The role of three phase bone scintigraphy in management of patients with chostochondral pain - Koc, Z.; Ozyurtkan, M.; Balci, T. (Springer, 2013)
[Abstract Not Available]
Annual Congress of the European-Association-of-Nuclear-Medicine (EANM) -- OCT 19-23, 2013 -- Lyon, FRANCE
Keywords: bone scintigrpahy; three phase; chostochondral pain